Principles of European constitutional law - Bogdandy, Armin von; Bast, Jürgen (Hart [u.a.], 2010)
This volume presents European constitutional law not as a theoretical construct but as binding law. While politicians wrestle with the Constitutional Treaty, this volume presents European constitutional law as it stands, setting out its theoretical and doctrinal fundamentals from the perspective of German-speaking scholarship